Taking small classes one step further - Finn, Jeremy D.; Wang, Margaret C. (Emerald Publishing Limited : Information Age Pub., 2002)
This volume on teaching small classes is divided into the sections: lessons learned about best teaching practices in small classes; implementing and supporting small class programmes; evaluating small class initiatives; and teachers voices.
Keywords: Class size -- United States.; School improvement programs -- United States.; Education -- Classroom Management.; Teaching skills and techniques.; elektronické knihy; electronic books